2021
DOI: 10.3390/jof7070509
|View full text |Cite
|
Sign up to set email alerts
|

Differential Physiological Prerequisites and Gene Expression Profiles of Conidial Anastomosis Tube and Germ Tube Formation in Colletotrichum gloeosporioides

Abstract: The conidia of a hemibiotrophic fungus, Colletotrichum gloeosporioides, can conventionally form a germ tube (GT) and develop into a fungal colony. Under certain conditions, they tend to get connected through a conidial anastomosis tube (CAT) to share the nutrients. CAT fusion is believed to be responsible for the generation of genetic variations in few asexual fungi, which appears problematic for effective fungal disease management. The physiological and molecular requirements underlying the GT formation versu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
3
7
0
Order By: Relevance
“…Our study has revealed that the conidia fusion rate (CFR) decreases as the nutrient concentrations in the habitat increases (Figures 3 and 4). This result is consistent with previous research and supports the idea that the formation of CF is closely related to the nutrient content of the habitat [21,23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study has revealed that the conidia fusion rate (CFR) decreases as the nutrient concentrations in the habitat increases (Figures 3 and 4). This result is consistent with previous research and supports the idea that the formation of CF is closely related to the nutrient content of the habitat [21,23].…”
Section: Discussionsupporting
confidence: 93%
“…Although the CFR of different species or strains had different responses to the nutrient content and composition of the habitat, the rule that the CFR was inversely proportional to the nutrient concentration of the habitat was confirmed for almost all species. Based on the above research, scholars speculated that another significance of CF might be an adaptation to nutrient deficiency in the habitat [23]. However, this hypothesis has not been supported by direct experimental data, and the way CF adapts to nutrient-poor environments is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Falcate conidia secrete mycosporines as germination inhibitors when present in high spore numbers, as in acervuli [14,15]. The formation of germling fusions is also dependent on spore densities; this has been documented for C. graminicola as well as several other fungi [15,26,[44][45][46]. In an earlier study, we observed a positive correlation between the formation of penetrating hyphopodia by oval conidia and the germling fusion process on leaves, indicating that the pathogenicity program of oval conidia is also dependent on the spore concentration [15].…”
Section: An Unknown Quorum-sensing Mechanism Regulates Hyphopodia For...mentioning
confidence: 99%
“…Fusion of vegetatively incompatible strains of fungi, including V. dahliae , usually triggers an incompatibility reaction that can cause cell death of the anastomosed compartments [54]. Based on the observations that this reaction in N. crassa is characterized by induction of ROS [57], and that genes involved in the OSR are up-regulated during CAT formation in Colletotrichum gloeosporioides [58], we used NBT staining to study O 2 •− accumulation in incompatible V. dahliae fusions (pairing Ls.17 H1-sgfp × 123V). One-third of such fusions (n = 30) exhibited increased formazan precipitation (Figure 7F), indicating that ROS accumulation is indeed associated with the onset of the incompatibility reaction, similarly to what was observed in N. crassa [57].…”
Section: Resultsmentioning
confidence: 99%